Risk and Protective Effects of Need for Approval on Self-Injury in Adolescent Girls. - Clapham, Rebekah B.; Ye, Zihua; Somerville, Leah H.; Miller, Adam Bryant; Giletta, Matteo; Hastings, Paul D.; Slavich, George M.; Nock, Matthew K.; Prinstein, Mitchell J.; Rudolph, Karen D. (Child Psychiatry & Human Development, 2026)
The goal of this research was to expand theoretical models of adolescent suicide by exploring whether individual differences in adolescent girls' need for approval (NFA and NFA) contribute to risk for, or protection against, self-injurious thoughts and behaviors (SITBs). We examined these novel hypotheses in a series of concurrent and longitudinal analyses in two samples of adolescent girls (Study 1: N = 89, M = 16.31 years, SD = 0.84, 67.4% White; Study 2: N = 229, M = 11.80, SD = 1.80, 49.8% White). Hierarchical linear and logistic regressions revealed that NFA was generally associated with higher risk for SITBs, whereas NFA generally had a protective effect against SITBs; moreover, the strength of these associations depended on the extent to which girls engaged in rumination. Together, these results suggest that encouraging girls to develop diverse foundations for their sense of self-worth beyond peer judgements may protect against SITBs.